PENGARUH REBUSAN DAUN SALAM (Syzygium polyanthum Wight) TERHADAP PENURUNAN KADAR ASAM URAT DALAM DARAH MENCIT (Mus musculus L.) JANTAN Strain Balb-C - Abil Fida Siskayanti; Joko Waluyo; Slamet Hariyadi (saintifika, 2017)
Uric acid is the final substance of purine breakdown which is assisted by guanase and xanthine oxidase enzymes. Excess blood uric acid levels are called hyperurosemia. Treatment is usually using synthetic drugs such as allopurinol which has side effects for the body, so it is necessary to take herbal remedies such as Syzygium polyanthum Wight which contains active ingredients such as flavonoids as an inhibitor of the xanthine oxidase enzyme. This study aims to determine the effect of giving Salam Leaf Decoction to the Decrease in Blood Uric Acid Levels. This study uses a completely randomized design study (CRD) with 5 repetitions. This study uses One Way Anova data analysis and continued with Duncan's Test. From the results of the study, at a dose of P1 (0.2 ml / 20 g WB), P2 (0.4 ml / 20 g WB) and P3 (0.8 ml / 20 g BB), a percentage of uric acid levels decreased 40.45% in group P1; 48.19% in the P2 group; 53.53% in the P3 group; 60.35% in the K + group; and -30.73% in the K-group. Of the 5 doses, the most effective dose to reduce uric acid levels in the blood is P2 dose (0.4 ml / 20g WB).